Analysis of User Satisfaction in the Test of English Proficiency Information System Service at UNESA Using the E-S-QUAL Method - Nasywa Putri Nataliza; Dwi Fatrianto Suyatno (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2026)
The Test of English Proficiency Information System SIMTEP at Universitas Negeri Surabaya is a technology-based service that plays an important role in supporting English proficiency testing; therefore, evaluating its service quality is essential to ensure user satisfaction. This study aims to analyze user satisfaction with SIMTEP services using the E-S-QUAL method through a quantitative approach. One hundred participants filled out surveys, and the results were evaluated using SEM—specifically, the Partial Least Squares (PLS) method. Total user happiness is classified as satisfied, according to the data, with an average satisfaction score of 3.99. Five of the seven hypotheses tested were shown to be true: system availability and remuneration did not significantly impact user happiness, but efficiency, fulfillment, privacy, responsiveness, and interaction did. Service efficiency, data privacy, ease of contact, responsiveness, and fulfillment accuracy are the primary factors that impact customer satisfaction with SIMTEP, according to these research. In addition to providing a foundation for future studies on electronic service quality and user satisfaction, this study is anticipated to provide an assessment reference for enhancing SIMTEP service quality.